Confidence, attitudes, beliefs and determinants of implementation behaviours among physiotherapists towards clinical management of low back pain before and after implementation of the BetterBack model of care - Karin Schröder; Birgitta Öberg; Paul Enthoven; Alice Kongsted; Allan Abbott (BMC, 2020)
Abstract Background Implementing clinical guidelines is challenging. To facilitate uptake, we developed a model of care (BetterBack Model of Care) and an implementation strategy to support management of low back pain in primary care. The aim of this study was to evaluate physiotherapists´ confidence, attitudes and beliefs in managing patients with low back pain before and after a multifaceted implementation of the BetterBack Model of Care. A further aim was to evaluate determinants of implementation behaviours among physiotherapists. Methods This clinical trial was an experimental before and after study within a hybrid type 2 effectiveness-implementation trial. The primary outcome was Practitioner Self-Confidence Scale (PCS), secondary outcomes were the Pain Attitude and Beliefs Scale for Physiotherapists (PABS-PT) and Determinants of Implementation Behaviour Questionnaire (DIBQ). Data was analysed using repeated measures ANOVA and pairwise comparisons. Results One hundred sixteen physiotherapists answered a questionnaire before, directly after, as well as 3 and 12 months after implementation of the Model of Care. PCS improved over time with a large effect size post implementation (η p 2  = 0.197, p < 0.001). Changes in PABS-PT were only significant after 12 months with higher biopsychosocial orientation, (η p 2  = 0.071, p < 0.01) and lower biomedical orientation, (η p 2  = 0.136, p < 0.001). Directly after the workshop, after 3 and 12 months, physiotherapists had high ratings on all DIBQ domains, (scores > 50) implying that all were potential facilitators of the implementation. However, after 3 months, all domains had significantly decreased except for organisation, social influence and patient expectation domains. However, after 12 months, organisation and social influence domains had significantly decreased while domains such as knowledge, skills and beliefs about capabilities returned to initial levels. Conclusions Physiotherapists´ confidence and biopsychosocial orientation increased after implementation and may have the potential to improve management of low back pain in primary care. The implementation behaviour showed mostly facilitating patterns but changed over time, pinpointing a need to repeatedly monitor these changes. This can inform the need for changes of implementation efforts in different phases and support sustainability strategies. Trail registration ClinicalTrials.gov NCT03147300 3 May 2017, prospectivly registered.